Screening of Custard apple (Annona squamosa L.) genotypes for Fruit rot resistance (Indian Journal of Arid Horticulture, 2023)
Custard apple (Annona squamosa L.) is a resilient dry land horticulture crop with significant export potential and good economic rewards. Fruit rot, caused by Colletotrichum gloeosporioides  Penz, is one of the major custard apple disease that can cause significant losses. The custard apple genotypes were screened by different methods at All India                           Co-Ordinated Research Project on Arid Zone Fruits (Fig and Custard apple), Jadhavwadi to find out source of resistance. It was observed that all 30 genotypes were found infected by disease.  The studies carried out by Attached Fruit Culture (AFC) revealed that more number of genotypes had shown highly susceptible reaction those inoculated by Mycelial Bit Inoculation Method (MBIM) than those inoculated by Micro Droplet Inoculation Technique (MDIT).  In by MBIM method, Vrudheshwar-3, Verul-2, Karkhel, Vrudheshwar-4,  Vrudheshwar-2, Telgaon Local,  Humnabad Local and  Dhanagarawadi-3  genotypes  showed moderately resistant reaction to disease whereas  in MDIT method, Vrudheshwar-3,  Verul-2 and Karkhel  showed resistant reaction. The custard apple genotypes were screened natural field condition also, out of 30 genotypes, Vrudheshwar-3, Verul-2, Karkhel,  Humnabad Local, Dhanagarwadi-3 and Vrudheshwar-4  recorded resistant reaction to fruit rot disease.
Keywords: Custard apple; fruit rot; Colletotrichum gloeosporioides; AFC; MBIM; MDIT